A Sustainability Criteria and Indicators Framework for Legacy Mine Land - Worrall, R.C.; Neil, D.T.; Brereton, D.; Mulligan, D.R. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
Sustainable development practices are an established part of most mining companies’ business activities. However, several challenges for the industry and regulators remain. Turning sustainable development rhetoric into tangible, sustainable outcomes for mine land remains an issue of contention. In part this can be attributed to the history of mining and the negative impacts it has had on the natural and social environment. Future mining activities, rightly or wrongly, will be judged against the legacies of the past and current poor performers. Legacy mine land, defined here as “land which has been mined and is now being used for another purpose, or is orphaned, abandoned or derelict and in need of remedial work” presents a management challenge, particularly in the context of sustainable development. A review of the situation in Australia suggests in excess of 30,000 sites exist. Globally, millions of such sites are likely to exist. Having criteria against which to measure progress toward or away from stated sustainable development goals is key to delivering results. The aim of this research was to develop a sustainability criteria and indicators framework derived from several resource sectors (including mining, forestry and agriculture) but tailored to suit the particular needs of legacy mine land. A case study area located in southeast Queensland, Australia has also been used to refine the criteria and indicators framework presented here. Outcomes from the research to date indicate that current planning regimes in Australia barely address legacy mine land, that there is inadequate communication between local and state government, and land re-use objectives (where they exist) may not deliver sustainable outcomes over long timeframes. We propose that these may be common themes throughout mining-dependent countries, developed or developing. Managing legacy mine land against a ‘sustainability criteria and indicators framework’ will equip stakeholders with tools that will be of growing use as mining activities increasingly intersect with local communities. The resulting framework consists of 14 criteria and 72 indicators, in contrast to some existing non-specific schemes which have in excess of 130 indicators.